Effect of Electrolyte Concentration in Electrochemical Deposition on Co-Ni-Fe Film Composition (Global Journals of Research in Engineering, 2023)
A study on electrochemical deposition in a triple-component Co-Ni-Fe system from a chloride electrolyte solution with equal concentrations of Co Ni and Fe was performed The concentrations used were 0 48 0 083 0 00625 mol l and the temperature was 70 The relative content of the components in the film approached the composition of the electrolyte when the concentration of each component was slightly decreased The dependence of the composition of films on the current density is explained by concentration polarization
Keywords: Co-N-Fe films; chloride electrolyte; partial ion current balance; electrochemical deposition